Anaesthetic and cardiorespiratory effects of ketamine plus dexmedetomidine for chemical restraint in black capuchin monkeys (Sapajus nigritus). Issue 2 (4th March 2018) - Chagas, JAB; Santos, LCP; Silva Filho, JR; Bondan, C
Abstract : AIMS: To evaluate the quality of anaesthesia and cardiorespiratory effects of ketamine and two doses of dexmedetomidine in captive black capuchin monkeys ( Sapajus nigritus ) undergoing routine clinical examination. METHODS: Twenty-four animals undergoing routine clinical examination were enrolled in the study. Animals were briefly physically restrained and examined to ensure no obvious illness was present and that they were healthy. Monkeys were randomly allocated to two groups (n=12 per group) and then treated with a combination of I/M 7.5 mg/kg ketamine and either 30 µg/kg or 50 µg/kg dexmedetomidine (Dex30 or Dex50 groups, respectively). Interval to onset and duration of anaesthesia were recorded, and the quality of induction of anaesthesia and recovery were subjectively evaluated. Heart rate, respiratory rate, systolic arterial pressure (SAP), rectal temperature, degree of sedation, analgesia, muscle relaxation and response to auditory stimulus were measured every 5 minutes from onset of anaesthesia until recovery. RESULTS: The mean interval to onset of anaesthesia was 7.3 (SD 6.6) and 9.1 (SD 5.0) minutes for the Dex30 and Dex50 groups, respectively (p=0.208). Mean duration of anaesthesia was longer for monkeys in the Dex50 (85.5 (SD 15.3) minutes) compared to those in Dex30 (63.9 (SD 16.4) minutes) group (p=0.003). Induction was considered excellent in 23/24 animals, and recovery was excellent in all animals. Heart rate, respiratory rate and body temperature decreased in both groups when compared to baseline, with no differences between groups. No differences between groups were found for assessments of sedation, analgesia, muscle relaxation or response to auditory stimulus. CONCLUSION AND CLINICAL RELEVANCE: Administration of ketamine and dexmedetomidine at the two doses produced adequate, dose-dependent chemical restraint, with excellent induction and recovery, and minimal clinically significant cardiorespiratory effects in captive capuchin monkeys. Due to the occurrence of arrhythmias, electrocardiographic monitoring is recommended when this combination is used. The administration of higher doses of dexmedetomidine produced longer lasting anaesthesia without further compromise of cardiorespiratory parameters.